2021
DOI: 10.1371/journal.pone.0259586
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with desmoglein 3 induces non-pathogenic autoantibodies in mice

Abstract: Background Pemphigus vulgaris (PV) is a rare autoimmune blistering disease characterized by the development of autoantibodies targeting desmoglein (Dsg) 3, but also against Dsg1 in mucocutaneous disease. Given that existing PV animal models only recapitulate aspects of the disease, we aimed to establish a more comprehensive disease model based on the immunization of mice with PV autoantigen(s). Methods The following immunization strategies were tested: (i) C57Bl/6J, B6.SJL-H2s C3c/1CyJ, DBA2/J, or SJL/J mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…However, they did not test the pathogenicity of the serum from recipient mice, including the presence of antibodies recognizing native Dsg3 19 . Notably, the adjuvants used in these studies were CFA, alum, 15,19 TiterMax 18 or unspecified 11 . We believe that the recent availability of vaccine adjuvants with excellent immune‐activation capabilities opens up possibilities for inducing Dsg3‐specific autoimmune responses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, they did not test the pathogenicity of the serum from recipient mice, including the presence of antibodies recognizing native Dsg3 19 . Notably, the adjuvants used in these studies were CFA, alum, 15,19 TiterMax 18 or unspecified 11 . We believe that the recent availability of vaccine adjuvants with excellent immune‐activation capabilities opens up possibilities for inducing Dsg3‐specific autoimmune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that antibodies induced by immunization with rDsg3 in wild-type mice, constrained by immune tolerance, failed to produce pathogenic antibodies capable of recognizing native Dsg3. [15][16][17][18] Notably, the adjuvants used in these studies were complete Freund's adjuvant (CFA), alum, 15,17,19 squalenebased TiterMax 18 or unspecified. 11 Although CFA based on mycobacteria remains the most potent immunopotentiator reported to date, 20 we believe that the recent availability of vaccine adjuvants with excellent immune-activation capabilities opens up possibilities for inducing Dsg3-specific autoimmune responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent endeavors to break tolerance against Dsg3 in various strains of Dsg3-expressing mice employing different immunization protocols with recombinant human and murine Dsg3/Dsg1 forms did not elicit a clinical phenotype while non-pathogenic anti-Dsg3/Dsg1 IgG was induced ( 115 ). However, unpublished work currently focuses on the establishment of a Dsg3-transgenic mouse model displaying the formation of HLA-dependent antigen-specific T and B cells as well as a solid antigen-specific IgG as a basis of a lasting clinical phenotype.…”
Section: Antigen-specific Immunization Of Mice To Induce B and T Cell...mentioning
confidence: 99%
“…This approach was taken because immunization of wild-type mice expressing Dsg3 does not lead to in vivo pathogenic autoantibodies. [46][47][48] Within a few days, autoantibody production is noted in the Rag2 -/recipient mice, which are maintained without further immunizations for six months. While lesions develop within 7-14 days after transfer, weight loss was evident mainly due to blisters in the oral mucosa, which was severe in some mice and caused their death.…”
Section: Model 4: Active Transfer Modelsmentioning
confidence: 99%